Uptake, toxicity, and maternal transfer of cadmium in the oribatid soil mite, Oppia nitens: Implication in the risk assessment of cadmium to soil invertebrates. (April 2020) - Fajana, Hamzat O.; Jegede, Olukayode O.; James, Kyle; Hogan, Natacha S.; Siciliano, Steven D.
Abstract: Cadmium (Cd) is a heavy metal of concern in contaminated sites because of its high toxicity to soil biota and humans. Typically, Cd exposure is thought to be dominated by dissolved Cd in soil pore water and, thus, dermal uptake. In this study, we investigated the uptake, toxicity, and maternal transfer of Cd in a standard soil invertebrate, the oribatid mite ( Oppia nitens ), which is common to boreal and temperate ecozones. We found total soil Cd predicted Cd uptake in adult and juvenile O . nitens with no significant uptake from pore water by juvenile mites. Cadmium significantly inhibited juvenile production and recruitment as well as reduced adult fecundity. Adult O . nitens maternally transferred 39–52% of their Cd body burden to juveniles (tritonymphs) while the maternally-acquired Cd accounted for 41% of the juvenile internal Cd load. Our results suggest that dermal adsorption of metal ions is not important for O . nitens and that maternal transfer of Cd in soil invertebrates has ecological and toxicological implications for populations of soil invertebrates. Maternal transfer should be incorporated as a criterion in setting environmental soil quality guidelines (SQGE ) for cadmium and other non-essential heavy metals. Graphical abstract: Image 1 Highlights: Oppia nitens do not accumulate cadmium (Cd) from soil water via dermal adsorption. Cd reduces fecundity and juvenile recruitment of O. nitens. Adult O. nitens maternally transferred 46% of its Cd body burden to juveniles. About 41% of Cd in juvenile mites is due to maternal transfer. Abstract : Adult Oppia nitens maternally transfer a significant portion of its cadmium body burden to juveniles, and this could cause transgenerational toxicity on the mite's population.